Physical Drivers of Biogeochemical Variability in the Polar Front Meander. Issue 6 (31st May 2022) - Yang, Xiang; Strutton, Peter G.; Cyriac, Ajitha; Phillips, Helen E.; Pittman, Nicholas A.; Vives, Clara R.
Abstract: The Southern Ocean plays a vital role in global ocean circulation, and the Polar Front (PF) is one of its most important physical features. The PF meander south of Tasmania, around 153°E, 55°S, is a very dynamic region which spawns mesoscale eddies, and influences local biogeochemistry and sea‐air interaction. By using voyage and ancillary data, we investigated the unusually strong spring bloom in the vicinity of the PF meander in 2018. We infer that the upwelling of deep water at the front and in eddies, brings macronutrients and dissolved iron (dFe) to the surface. Chlorophyll concentration peaked at over 0.6 mg m −3, which is anomalously high for this area. With reduced iron limitation, the physiological characteristics of phytoplankton in the northern, downstream part of the study area also changed. The photochemical efficiency was improved and released this area from its usual high‐nutrient low‐chlorophyll (HNLC) status. This was mainly indicated by the increase in the dawn Fv/Fm maximum (indictor of photochemical efficiency) from 0.2 to over 0.5. With the biomass increase and healthier community status, we observed consumption of surface dissolved inorganic carbon and increased particulate organic carbon production to about 40 μmol L −1, forming a weak local carbon sink. Through the investigation of multiple years, a weak positive correlation between mixed layer depth shoaling and phytoplankton growth was found, but there was significant interannual variability in this relationship, likely caused by variable eddy conditions and dFe delivery. Plain Language Summary: Eddies are circulating ocean features with a diameter of about 100 km, which last for weeks to months. At any given time, there are about 1, 300 eddies in the Southern Ocean. Eddies transport, mix, and stir nutrients (like nitrate, silicate, and dissolved iron) which can influence local biological processes. Using data from a voyage in the Southern Ocean south of Tasmania, we investigated a spring phytoplankton bloom promoted by local physical processes like eddy formation. With the lifting of iron limitation, we found that the biomass here increased rapidly in a short time, and the phytoplankton became healthier. As a result of this, surface dissolved carbon was consumed, and organic carbon production increased. Based on a 20‐year retrospective satellite study, a positive relationship between mixed layer depth shoaling and biomass increase was revealed, but strong interannual variability also existed. Key Points: An unusually strong spring bloom was observed in a highly unstable Polar Front meander south of Tasmania Physiological characteristics of phytoplankton, measured by fluorescence, identified iron‐sufficient and iron‐deficient regions The strong bloom was likely favored by local and recent mixed layer variability and mesoscale processes, and created a local carbon sink